Survival Rate and Growth of Fighting Fish Larvae (Betta splendens Regan) Fed on Various Live Foods - T. Budiardi; T. Nursyams; Agus Oman Sudrajat (Jurnal Akuakultur Indonesia)
Larval of fighting fish (Betta splendens Regan) requires precise live foods for its growth and survival. In this experiment, fish larvae were fed on either Paramecium + Artemia, Paramecium + Artemia + Tubifex, Paramecium + Moina, or Paramecium + Moina + Tubifex. The fish were fed Paramecium from day-2 till day-7 after hatching. There after, the live food was changed according to the treatments till day-28.  Results showed that fish fed on Paramecium + Artemia significantly had the highest total length (12.63 mm) than other treatments (11.86 mm). On the other hand, survival rate of fish had no significant affected by the treatments.